2020
DOI: 10.3390/ijerph17031124
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Medical Resource Use in Patients with Osteoporosis and Depression: A Cross-Sectional Analysis from the National Health and Nutrition Examination Survey

Abstract: Background: Patients with either osteoporosis or depression are prone to develop other diseases and require more medical resources than do the general population. However, there are no studies on health-related quality of life (HRQoL) and medical resource use by osteoporosis patients with comorbid depression. We conducted this study for clarifying it. Methods: This cross-sectional study from 2005 to 2010 (6 years) analyzed 9776 National Health and Nutrition Examination Survey (NHANES) patients > 40 years old. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
0
15
0
1
Order By: Relevance
“…However, studies focusing on vitamin D and bone in GEP-NETs are missing. Weak or indirect effects on bone are described for depression, low physical activity, as well as specific miRNAs (miRNA-210, -21 and -196a) [56,57,83,130]. Finally, specific aspects of MEN1 syndrome, including primary HPT and gastrinoma, have been shown to worsen BMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies focusing on vitamin D and bone in GEP-NETs are missing. Weak or indirect effects on bone are described for depression, low physical activity, as well as specific miRNAs (miRNA-210, -21 and -196a) [56,57,83,130]. Finally, specific aspects of MEN1 syndrome, including primary HPT and gastrinoma, have been shown to worsen BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with recurrent disease reported significantly higher anxiety, impaired overall physical function, impaired sleep, and significant fatigue compared to those with no current NET [82]. It has been reported that in patients with depressive disorder, the duration of the disease negatively correlates with BMD and physical activity, which, in turn, significantly reduces the HRQoL [83]. Moreover, low physical activity is associated with an increased risk of osteoporosis [84].…”
Section: Impact Of Quality Of Lifementioning
confidence: 99%
“…However, there are no studies on health-related quality of life (HRQoL) and medical resource use by osteoporosis patients with comorbid depression. The first paper, “ Health-Related Quality of Life and Medical Resource Use in Patients with Osteoporosis and Depression: A Cross-Sectional Analysis from the National Health and Nutrition Examination Survey ”, by Weng et al [ 21 ], uses multivariate linear and logistic regression model to analyze the HRQoL and medical resource use between groups. Each patient was assigned to one of four groups: osteoporosis-positive (+) and depression-positive (+) (O + /D + ); O + /D − ; O − /D + ; O − /D − .…”
Section: The Organization Of This Special Issuementioning
confidence: 99%
“…Well-known risk factors are: biological predisposition, gender, age, positive family history, low body weight and bad habits (smoking, taking alcohol, fast food, greasy and poor-quality food, lack of physical activity) as well as the use of certain medications (etc. corticosteroids) [6,7]. In addition to those risk factors, it is not clear whether the same pathophysiological processes take place in mood disorders and osteoporosis [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Common facts that prove the existence of common pathophysiological processes in both disorders are considered to be hypercortisolemia, increased activity of the hypothalamicpituitary-adrenal axis, increased cytokine activity (interleukin-6 (IL-6) and tumor necrosis factor (TNF)), and decrease in anti-inflammatory interleukin activity (IL-10, IL-13) as well as an increase in oxidative stress factors, increase in parathyroid hormone levels with consecutive decrease of 25 (OH) D vitamin, and the decrease in estrogen levels in plasma [6,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%